Historical significance of tribal Tamgas and its relation to the runic script - Abdykulova G., Shnanov U.R., Artykbaev Z. O., Kazhenova G. T., (Opción, 2020)
This article studies the traditions of the Tamga and comprehensively examines its nature and significance for the peoples of Central Asia. The research presents interpretation of specific arguments and research reviews regarding the scope of Tamga use. By shedding light on the role of the Tamga in different tribes in terms of studying the ethnic history, the article considers the scientific concepts on formation and use of symbols. Studying the Tamga reveals its role in addressing the social issues. The common features that the Tamgas of different Turkic peoples have indicate the ethnic kinship between them.